2022
DOI: 10.3390/nu14214576
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antimicrobial Activities of Portuguese Prunus avium L. (Sweet Cherry) By-Products Extracts

Abstract: The bioactivity of natural by-products in food and pharmaceutical applications is the subject of numerous studies. Cherry production and processing generates large amounts of biowaste, most of which is not used. The recovery of these by-products is essential for promoting the circular economy and to improving sustainability in the food industry. In this work, we explored the anti-inflammatory and antimicrobial potential of two different extracts from stems, leaves, and flowers of Portuguese cherries. The anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…The results obtained were compared with those of other studies: P. avium leaf and stem extracts, as reported by Nunes et al, showed inhibitory activities (IC 50 ) against NO • of 183 and 111 mg/L, respectively. These results were significantly lower than those obtained in the present study [57]. In addition, the result for the NO • uptake capacity of the cherry stem obtained by Agulló-Chazarra et al was considerably lower than that obtained by us [26].…”
Section: Evaluation Of Antioxidant and Antiradical Activitiescontrasting
confidence: 90%
“…The results obtained were compared with those of other studies: P. avium leaf and stem extracts, as reported by Nunes et al, showed inhibitory activities (IC 50 ) against NO • of 183 and 111 mg/L, respectively. These results were significantly lower than those obtained in the present study [57]. In addition, the result for the NO • uptake capacity of the cherry stem obtained by Agulló-Chazarra et al was considerably lower than that obtained by us [26].…”
Section: Evaluation Of Antioxidant and Antiradical Activitiescontrasting
confidence: 90%
“…Among fruits, sweet cherry phenolic-rich fractions can reduce nitric oxide radicals and decrease iNOS and COX-2 expression in RAW macrophages stimulated with lipopolysaccharide [30]. Moreover, aqueous and hydroethanolic extracts of their vegetal parts also are effective in inhibiting nitrite levels in a dose-dependent manner in these cell lines [28]. Moreover, some Brazilian plants also showed potential to reduce TNF-α and CCL2 levels in lipopolysaccharide-stimulated human monocytic THP-1 cells [275].…”
Section: Anti-inflammatory Abilitiesmentioning
confidence: 99%
“…Among the new and most promising availability strategies, special attention has been given to bioactive molecules largely found in nature, namely, polyphenols, since their chemical structure with catechol methoxy and pyrogallol groups confer them notable health benefits, like antioxidant, anti-inflammatory, anti-bacterial, and antiproliferative activities, as well as the capacity to prevent neurological and cardiovascular pathologies, promote gastrointestinal health and vision without, it is believed, side-effects, and enhance wound healing [14][15][16][17][18][19][20][21][22][23]. In addition, polyphenols are also easier to obtain, water-soluble, and more economical than chemical drugs, and have already shown effectiveness in inhibiting JAK proteins and JAK/STAT signaling pathways [24][25][26][27][28]. Particularly, curcumin displayed the capability to relieve rheumatoid arthritis progression by suppressing inflammatory responses, synovial hyperplasia, and protein expression levels of phosphorylated JAK2 and STAT3 in mice with the collagen-induced arthritis model that were treated at a dose of 100 µM curcumin/day for almost three months [29], while in docking studies, salvianolic acid C exhibited a great binding affinity for JAK (10.7 kcal/mol) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on the fruits and leaves of different varieties of sweet and sour cherries showed that the bioactive compounds exhibited a high potential to inhibit the chemical substrates of enzymes related to diabetes [24,25]. Other by-products of Portuguese sweet cherry (P. avium L.), i.e., flowers, leaves, and stems, were good sources of phenolic extracts with anti-inflammatory activity found in murine RAW 264.7 macrophages, and presented antimicrobial potential against Gram-positive bacterial strains [26], with antidiabetic and anti-hemolytic potential [27]. No studies on the effect of bitter cherry extracts on NAFLD were found.…”
Section: Introductionmentioning
confidence: 99%